2014
DOI: 10.1186/1741-7015-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction therapy with bortezomib and dexamethasone followed by autologous stem cell transplantation versus autologous stem cell transplantation alone in the treatment of renal AL amyloidosis: a randomized controlled trial

Abstract: BackgroundAlthough the use of bortezomib alone and in combination with steroids has shown efficacy in AL amyloidosis, its role in combination with high-dose melphalan and autologous stem cell transplantation (HDM/SCT) is unknown. In this study, we evaluated bortezomib in combination with dexamethasone (BD) for induction chemotherapy prior to HDM/SCT.MethodsThis was a single-center, prospective, randomized controlled trial comparing induction therapy consisting of two BD cycles followed by HDM/SCT (BD + HDM/SCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
54
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 44 publications
2
54
0
1
Order By: Relevance
“…13 Some more recent studies, however, support the role of PI or IMiD-based induction in improving outcomes after auto-HCT. 12 The significance of reduction of FLC as a predictor of survival was first reported by Dispenzieri et al 14 A recent report from the National Amyloidosis Center in the United Kingdom identified the magnitude of the FLC response at 6 months from baseline as a strong predictor of PFS and OS. 15 HD melphalan is nephrotoxic, and some studies have reported a high risk of renal toxicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Some more recent studies, however, support the role of PI or IMiD-based induction in improving outcomes after auto-HCT. 12 The significance of reduction of FLC as a predictor of survival was first reported by Dispenzieri et al 14 A recent report from the National Amyloidosis Center in the United Kingdom identified the magnitude of the FLC response at 6 months from baseline as a strong predictor of PFS and OS. 15 HD melphalan is nephrotoxic, and some studies have reported a high risk of renal toxicity.…”
mentioning
confidence: 99%
“…Huang et al 12 conducted a randomized clinical trial where patients either received induction with bortezomib+dexametha-sone or no induction before HD melphalan and auto-HCT. Renal response at 2 years was 75% in the induction arm and 53% in the non-induction arm.…”
mentioning
confidence: 99%
“…5,6 Treatment with bortezomib pre-AHCT has been shown to improve transplant eligibility for patients, previously considered to be too high risk for AHCT, and may increase the response rates following AHCT. [7][8][9][10] Herein, we describe our experience using bortezomib prior to AHCT and demonstrate the feasibility of this approach.…”
mentioning
confidence: 99%
“…[8][9][10]15 Overall, the collective experience of bortezomibbased induction prior to AHCT shows that it is a feasible approach for most patients who are otherwise candidates for transplantation and leads to favorable long-term outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation